2009
DOI: 10.1093/brain/awp169
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of intraneural perineurioma--a benign, focal hypertrophic neuropathy of youth

Abstract: The natural history of intraneural perineurioma has been inadequately studied. The aim of this study was to characterize the clinical presentation, electrophysiologic and imaging features and outcome of intraneural perineurioma. We ask if intraneural perineurioma is a pure motor syndrome that remains confined to one nerve and should be treated by surgical resection. We examined the nerve biopsies of cases labelled perineurioma and selected those with diagnostic features. Thirty-two patients were identified; 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
119
1
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(128 citation statements)
references
References 35 publications
3
119
1
5
Order By: Relevance
“…Medial Elbow Mass in an 18-year-old Woman 2159 [13]. Our patient presented with the chief complaint of paresthesias and had 4/5 weakness with small finger abduction on physical examination.…”
Section: Discussion and Treatmentmentioning
confidence: 78%
See 3 more Smart Citations
“…Medial Elbow Mass in an 18-year-old Woman 2159 [13]. Our patient presented with the chief complaint of paresthesias and had 4/5 weakness with small finger abduction on physical examination.…”
Section: Discussion and Treatmentmentioning
confidence: 78%
“…[6,12,13]. In one study, a predilection for the upper extremity was reported [6]; however, research has found a nearly equal incidence of upper and lower extremity involvement [12][13][14]. The definitive cause of these tumors is still being investigated [5,10].…”
Section: Discussion and Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The present case report represents a strategy on how to investigate a peripheral nerve problem with impaired function irrespective of location 3, 4. There was a long‐standing history of impaired function; an early sign was the delayed walking ability compared to the twin sister.…”
Section: Discussionmentioning
confidence: 96%